How Do Profitability and ISO 14001 Certification Impact on Sustainability Reporting? - Susi Handayani; Ni Nyoman Alit Triani; Mazurina Mohd Ali (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2024)
ntroduction/Main Objectives: The research aims to explain how Profitability and ISO 14001certification impact sustainability reporting. The extent of disclosure in sustainability reporting wasinfluenced by several things, including Profitability and ISO 14001 certificate. It was crucial formining companies and the primary and chemical sectors that negatively impact the environment andsociety. Background Problems: Companies were concerned about economic growth, socialdevelopment, and environmental welfare. Profitability was a measure of company performance, andthe ISO 14001 certificate was a reward for implementing the triple bottom line. Activities related toGCG and CSR could be reported separately by the company on the company's website or in theannual report and sustainability report. Research Methods: This study uses dummy variables for thedependent variable sustainability reporting, so the study used logistic regression analysis. This studyuses a sample of mining and elemental and chemical industry companies whose operationssignificantly impact the environment. Finding/Results: The study results explain that profitabilitydid not affect sustainability reporting because some profitable companies consider it unnecessary todisclose non-financial information. In contrast, companies that experience losses focus on thecompany's financial performance. On the other hand, the ISO 14001 certification obtained by thecompany, which means that the company had carried out environmental management, had a positiveimpact in that the company discloses sustainability reporting. Conclusion: The ISO 14001certification had the ability to explain sustainability reporting.